Identifikasi Flavonoid Dari Tanaman Dewandaru (Eugenia Uniflora L.) Dengan Metode Spektrofotometri Uv – Vis : Literatur Review Articel - Ermi Arbiyani; Abdul Aziz; Ina Nurunnisa; Muhamad Gilang; Muhamad Zein Latif (Peneliti.net, 2023)
Dewandaru (Eugenia uniflora L.) is a plant from the Myrtaceae family. The content of secondary metabolites in the dewwandaru plant is very diverse, one of which is flavanoid. The purpose of this study was to determine the content of flavonoids contained in the dewadaru plant by UV-VIS spectrophotometry. The method used in this paper is the literature review (LRA) method by collecting data from various scientific journals: Google Scholar, , Researchgate, ScienceDirect, Pubmed, Publons. The results obtained from this study are one of the types of flavonoids found in dewandaru leaves, namely 5,7,3',4'- tetra hydroxy flavonol or quercetin.